Flotation of coarse coal particles in the Reflux™ Flotation Cell. (1st April 2020) - Sutherland, J.L.; Dickinson, J.E.; Galvin, K.P.
Highlights: High fractional recoveries over an extended −2 +0 mm particle size band. Recoveries confirmed by discrete tracer particle addition and real feed experiments. Coarse particle recovery increased with decreasing gas flux. Coarse tracer particle recovery independent of feed flux. Recoveries upheld using counter-current washing in an inverted fluidized bubbly bed. Abstract: Froth flotation is a separation process that has widespread application throughout the coal and minerals industries. Conventional flotation technologies are effective in recovering coal up to about 0.35 mm and dense minerals up to about 0.10 mm. There are significant benefits to both the coal and minerals industries in increasing the upper particle size. This paper reports on an investigation of coarse coal flotation up to a nominal 2 mm size using the Reflux Flotation Cell (RFC). The first part of the investigation involved the flotation of coal tracer particles added to the system individually, with the RFC operating at a specific hydrodynamic condition defined by the feed and gas fluxes. The particles were strongly hydrophobic, having relative densities (compared to water) within the range 1.25 – 1.30. The particles were saturated by the collector, diesel oil, prior to each experiment to ensure consistent hydrophobicity. The tracer particle experiments revealed a general trend of decreasing coarse particle yield with increasing gas flux. The yields were highest at gas fluxes below 0.5 cm/s, and largely independent of the volumetric feed flux over the range 0.9 to 6.0 cm/s. The data revealed a dependence on the gas volume fraction in the overflow, with the highest recoveries observed when held at nominally 0.80 or less. The second part of the investigation involved the flotation of industrial coal slurry at 5 wt% solids concentration. The performance of the RFC was judged with reference to Tree Flotation for particles below 0.125 mm, and Float/Sink separation at a relative density of 1.6 for particles −2.0 +0.125 mm. Again, high recoveries of 82% to 97% for fractional sizes spanning −2.0 +0.125 mm were achieved provided the gas flux was below 0.5 cm/s. Product grade surpassed the tree curve using inverted fluidization water, without any recovery losses over the full particle size range.